2021
DOI: 10.1021/acs.energyfuels.1c01334
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Adsorption and Transport behavior of Gases in Moist Coal Matrix

Abstract: Water is ubiquitous in coalbeds, and its influence on coalbed carbon sequestration and/or methane recovery cannot be neglected. To investigate the roles of moisture content in gas transport and adsorption behavior, this paper presents a mass transport model for real gas transport in moist coal matrix based on multiple transport mechanisms. A modified kinetics in conjunction with Langmuir isotherm is proposed to incorporate the effects of moisture, and it is used to describe the mass change between bulk phase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Based on the principle of mass conservation, the mass balance equation for a free gas in porous matrices can be expressed as (Chen et al, 2020b(Chen et al, , 2021Cui et al, 2022): where…”
Section: Free Gas Diffusion In Coal Matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the principle of mass conservation, the mass balance equation for a free gas in porous matrices can be expressed as (Chen et al, 2020b(Chen et al, , 2021Cui et al, 2022): where…”
Section: Free Gas Diffusion In Coal Matricesmentioning
confidence: 99%
“…where τ is tortuosity of the porous medium, d f is the fractal dimension of the pore surface accounting for the effect of pore-surface roughness. Following the work by Chen et al (2021), the viscous flow-induced diffusivity D v can be expressed as:…”
Section: Free Gas Diffusion In Coal Matricesmentioning
confidence: 99%
“…Day and Ozdemir showed that moisture can change the heat of adsorption. Based on the exponential decay equation, Chen further proposed a relationship between the Langmuir pressure and the moisture content P normalL = P Lg + P normalL normalw .25em exp ( ξ ω ) where P Lg is the pressure constant unaffected by moisture, P Lw is the fraction that can be affected by moisture adsorption, and ξ is a weighting factor representing the role of moisture in gas adsorption.…”
Section: Apparent Permeability Model For Gas Transport In Moisture-po...mentioning
confidence: 99%
“…Wang reported that the presence of moisture occupies a portion of the pore space and diminishes the gas adsorption sites of coal, which lowers the amount of gas adsorption. Recent studies have shown that the Langmuir volume drops with increasing intrinsic moisture content, and the exponential equation may be used to describe the relationship between the amount of methane adsorption and intrinsic moisture content.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that gas adsorption in the internal pores of rock matrices is one of the important gas storage mechanisms in coal or shale reservoirs, and the adsorption capacity influences the gas content of these reservoirs. , The amount of adsorbed gas in coal or shale can be influenced by several controlling factors, such as coal type, pressure, temperature, and moisture content. However, gas adsorption, generally, is not a fully reversible process. Experimentally measured adsorption isotherms do not coincide with corresponding desorption isotherms determined over the same pressure range on the same samples.…”
Section: Introductionmentioning
confidence: 99%